2015
DOI: 10.1016/j.psyneuen.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Number of X-chromosome genes influences social behavior and vasopressin gene expression in mice

Abstract: Summary Sex differences in behavior are widespread and often caused by hormonal differences between the sexes. In addition to hormones, the composition and numbers of the sex chromosomes also affect a variety of sex differences. In humans, X-chromosome genes are implicated in neurobehavioral disorders (i.e. fragile-X, autism). To investigate the role of X-chromosome genes in social behavior, we used a mouse model that has atypical sex chromosome configurations resembling Turner (45, XO) and Klinefelter syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
(65 reference statements)
1
26
0
Order By: Relevance
“…There is some evidence for this in animal models with altered numbers of sex chromosomes, as well as from aneuploid individuals with increased risk for ASD (XYY, XXY, XXYY, XXY) [6,5557]. However, aneuploid individuals are relatively rare and often also exhibit sex hormone dysregulation, so these studies can be difficult to interpret, i.e.…”
Section: Sex Chromosome Theory: Is XX Protective or Is Xy A Risk Factor?mentioning
confidence: 99%
“…There is some evidence for this in animal models with altered numbers of sex chromosomes, as well as from aneuploid individuals with increased risk for ASD (XYY, XXY, XXYY, XXY) [6,5557]. However, aneuploid individuals are relatively rare and often also exhibit sex hormone dysregulation, so these studies can be difficult to interpret, i.e.…”
Section: Sex Chromosome Theory: Is XX Protective or Is Xy A Risk Factor?mentioning
confidence: 99%
“…To better understand the mechanisms by which sex-chromosome aneuploidies impact phenotypes, various animal models of KS or TS have been developed (Burgoyne and Arnold, 2016; Cox et al, 2014; Lue et al, 2010; Wistuba, 2010). Behavioral studies of these models indicate that both KS and TS aneuploidies impact learning, impulsivity and/or attention (Chen et al, 2013b; Cox et al, 2015; Davies et al, 2005, 2007; Isles et al, 2004; Lewejohann et al, 2009; Lue et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Obvious possible candidates include Y chromosome genes expressed in males, or a double dosage of X chromosome genes (particularly those that escape X inactivation) in females (Arnold, 2012). In one approach to address this issue, Cox and colleagues (2015) recently demonstrated that mice with only one X chromosome (X0 or XY) have more vasopressin expression in the amygdala and are less social than those with two X chromosomes (XX or XXY), pointing to the dosage of X chromosome gene(s) as responsible for these effects. Because the X chromosome is inherited asymmetrically (female offspring receive an X from both the mother and father, whereas male offspring receive an X only from the father), genes that are parentally imprinted, i.e.…”
Section: Gonad-independent Effects Of the Sex Chromosomesmentioning
confidence: 99%